Anti-democratic revolutionaries or democratic reformers? A review essay of Janek Wasserman's The Marginal Revolutionaries: How Austrian Economists Fought the War of Ideas - Stefan Kolev (The Review of Austrian Economics, 2020)
This paper provides a critical reading of Janek Wasserman's The Marginal Revolutionaries: How Austrian Economists Fought the War of Ideas. Wasserman depicts the evolution of the Austrian School from the 1860s until today, a particularly illuminating narrative for the readers of this journal. The breadth of portrayed economists, their cultural embeddedness in Austrian and US contexts, and the complexity of configurations across the school's generations create a rich and readable story. The last third of the book suffers from allegations about the ideological agenda and institutional power of the Austrian economists which sometimes lack sufficient substantiation. The paper indicates how both in their theorizing and in their political activities, the Austrian economists can be seen as reformers instead of revolutionaries, and as constitutionalists instead of anti-democrats. Despite these disagreements, Wasserman's portrayals evoke largely fair and challenging impulses both to scholars working in the Austrian research program and to those interested in the Austrian School's long history, regardless of one's ideological positions.
Keywords: A11; B13; B25; B31; F53; 330; Austrian school; Central European history; Neoliberalism; Ideas and institutions; Role of economists